Pengaruh Kesehatan Reproduksi Wanita dan Pemberdayaan Wanita Terhadap Tingkat Partisipasi Angkatan Kerja Wanita di Indonesia - Putri, Riri Eka; Ariusni, Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This study aims to find out and analyze how the influence of women's reproductive health and women's empowerment on the participation rate of the female workforce in Indonesia. This study used secondary data sourced from the Indonesian Central Bureau of Statistics with the research variables grouped into two parts, namely the bond variable which in this study was determined as the female labor force participation rate and the independent variables consisting of women's life expectancy, young women's marriage, female mother, female education level, female per capita income and female involvement in parliament. This study uses panel data regression analysis with the selected method, namely the Common Effect Model (CEM). The results showed that women's life expectancy, young women's marriage, women's fertility rates and women's involvement in parliament each had a negative and insignificant effect on women's labor force participation. Women's education level has a negative and significant effect on female labor force participation and women's per capita income has a positive and significant effect on female labor force participation.